Avaliação da utilização de resíduo gerado em sistemas úmidos de filtragem particulados de fundição como matéria-prima na construção civil: estudo em tijolos de cerâmica vermelha - Agnario dos Santos Moreira (2006)
This work intends to evaluate the viability of application of a pasty residue called mud of the hydro filters generated in great amount, 2.000 ton per month, in the water treatment station of gases washing in exhaustion systems and filtering by humid via ( hydro filters ) of acasting industry in the manufacture of red ceramics bricks.In this sense, samplings and laboratory analyses had been carried through for the complete residue characterization in terms of composition and toxicity in accordance with ABNT norms. As well as the study of the productive process of the residue generator.The bricks had been produced, in the normal conditions of the field, in the mixture ratios of 10, 20 30 40 and 50% of residue in relation to the clay. Such bricks had been submitted to all the tests of performance demanded by norm, whose results had been compared with thoseproducts without residue addition, of the same representative sampling.The generated fragments in the functionality assays of the produced devices with residue addition had been submitted the assays of solubility and leaching for verification of its behavior under the compared ambient point of view with others without residue addition.From the carried through studies, it can be concluded that concerning the technician performance it is possible to add up to 30% of the residue to the natural clay mass and the ceramic blocks remain inside of the acceptable band of performance established for the techniques norms. Concerning the ambient behavior, it was evidenced that up to 20% ofresidue addition to the natural clay mass keeps the produced bricks with characteristics of inert residue (Class IIB) according to NBR 10004:2004.As it is about a great volume, its application in substitution to the natural components of the devices of the civil construction will propitiate a significant ambient profit for preventing the extraction of correspondent amount directly of the nature and also for preventing its disposal in dump;